EKSTRAKSI MINYAK KACANG TANAH (PEANUT OIL) DENGAN PELARUT ETANOL DAN N-HEKSAN - Desma Rina; Syamsul Bahri; Zulnazri Zulnazri (LPPM Universitas Malikussaleh, 2021)
Peanut is one of the sources of vegetable oil, the oil content is very high, less than 65% compared to copra which contains more or less 45% oil (Sari, 2006). This study aims to analyze the value of oil yield, density, viscosity, water content, and acid number of peanut oil produced from groundnut seeds. Based on the research that has been used, the variable solvent volume varies from 400 to 600 mL, the extraction temperature variable used is 75oCand 80oC, and the time variable varies from 2- 4 hours. The resulting extraction is distilled using 80oC and 85oC temperatures to separate the oil from the solvent. This research was carried out by extracting sohklets using different solvents, ethanol and n-hexane. From the results of this study, the highest percentage of oil was 58.29% with n-hexane solvent, density of 1.122 gr / mL, viscosity of 0.1029 cP, moisture content of 6%, and acidity rate of 2 mg NaOH / gr of oil . Based on the research that has been done, it can be concluded that the volume of the solvent and the extraction time greatly affect the yield value of the oil produced, density, viscosity, moisture content, and acid number.